Malignant Rhabdoid Tumor of the Mediastinum: A Rare Variant of Thymic Carcinoma Presenting As Superior Vena Caval Syndrome - MD, Muniraju Maralakunte; MD, Lokesh Singh; MD, Uma Debi; MBBS, Tanka Karki; MD, Divya Aggarwal; MD, Amanjit Bal (Archives of Clinical and Medical Case Reports, 2020)
Malignant rhabdoid tumor (MRT) of the thymus is rare aggressive tumor and only 34 cases are reported in the literature till date. Index case report describes a middle adult, female, with superior vena caval syndrome and prevascular space mass on chest axial scan, and histological features revealing MRT of thymus and metastatic spread. Contrast-enhanced CT neck and chest revealed aggressive tumor causing severe narrowing of the right internal jugular and superior vena-caval junction. This case represents an example to consider MRT along with other tumors like lymphoma, germinoma and anaplastic carcinoma of thyroid in subjects with aggressive prevascular space mass, and to consider biopsy specimen evaluation rather aspiration cytology evaluation for evaluation of mediastinal masses.